(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The application of welding processes during manufacturing of metallic products result in changes of the properties of the base materials. Process simulation enables evaluation of the effect of heat application in proximity to the weld seam. The availability and use of input data, relevant for the specific material, is essential for the reliability of the results. The thermal characteristics of the materials, required for the heat modelling were identified. Their dependency on the material temperature was investigated and the formulas were presented. Particular values were found in existingdata sources, for specific structural steels, stainless steels, nickel and titanium alloys. The values of the thermal characteristics were represented and in graphical and tabulated formats, facilitating direct implementation in calculations, assessment of variation trends and applicability for specific purposes.